Clinical application of next generation sequencing for Mendelian disease diagnosis in the Iranian population - Ayda Abolhassani; Zohreh Fattahi; Maryam Beheshtian; Mahsa Fadaee; Raheleh Vazehan; Fatemeh Ahangari; Shima Dehdahsi; Mehrshid Faraji Zonooz; Elham Parsimehr; Zahra Kalhor; Fatemeh Peymani; Maryam Mozaffarpour Nouri; et al. (npj Genomic Medicine, 2024)
Abstract Next-generation sequencing (NGS) has been proven to be one of the most powerful diagnostic tools for rare Mendelian disorders. Several studies on the clinical application of NGS in unselected cohorts of Middle Eastern patients have reported a high diagnostic yield of up to 48%, correlated with a high level of consanguinity in these populations. We evaluated the diagnostic utility of NGS-based testing across different clinical indications in 1436 patients from Iran, representing the first study of its kind in this highly consanguineous population. A total of 1075 exome sequencing and 361 targeted gene panel sequencing were performed over 8 years at a single clinical genetics laboratory, with the majority of cases tested as proband-only (91.6%). The overall diagnostic rate was 46.7%, ranging from 24% in patients with an abnormality of prenatal development to over 67% in patients with an abnormality of the skin. We identified 660 pathogenic or likely pathogenic variants, including 241 novel variants, associated with over 342 known genetic conditions. The highly consanguineous nature of this cohort led to the diagnosis of autosomal recessive disorders in the majority of patients (79.1%) and allowed us to determine the shared carrier status of couples for suspected recessive phenotypes in their deceased child(ren) when direct testing was not possible. We also highlight the observations of recessive inheritance of genes previously associated only with dominant disorders and provide an expanded genotype–phenotype spectrum for multiple less-characterized genes. We present the largest mutational spectrum of known Mendelian disease, including possible founder variants, throughout the Iranian population, which can serve as a unique resource for clinical genomic studies locally and beyond.